TaPR1 Interacts With TaTLP1 via the αIV Helix to Be Involved in Wheat Defense to Puccinia triticina Through the CAPE1 Motif - Wang, Fei; Shen, Songsong; Zhao, Cunpeng; Cui, Zhongchi; Meng, Linshuo; Wu, Wenyue; Liu, Daqun; Wang, Haiyan (Frontiers in Plant Science, 2022)
Pathogenesis-related (PR) proteins play important roles in plant defense response and systemic acquired resistance (SAR). PR1 has antifungal activity against many plant pathogens. In our previous study, RNA sequencing (RNA-seq) was conducted on resistant wheat line TcLr19 and sensitive wheat cultivar Chinese Spring inoculated with Puccinia triticina (Pt) race PHNT. In this study, seven salicylic acid (SA)-induced TaPR1 genes involved in plant disease resistance were found in the RNA-seq library. Quantitative PCR (qPCR) results showed that TaPR1-4 was most induced by Pt among these seven TaPR1 genes in the incompatible interaction. Yeast two-hybrid (Y2H) results showed that TaPR1-4 interacted with TaTLP1 via the αIV helix. Protein-mediated phenotyping assays in vivo and antifungal activity in vitro demonstrated that wheat leaves infiltrated with pure TaPR1-4 protein developed significantly less disease compared to control leaves. This effect was correlated with a strong increase in defense gene expression, and resistance activity was dependent on the CAPE1 motif located in the C-terminal region of TaPR1-4. These findings increase current knowledge regarding the interaction of TaPR1 and TaTLP1 and provide new insights on the role of TaPR1 protein in the resistance of wheat to Pt.